2009
DOI: 10.1097/brs.0b013e3181995ec2
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ewing Sarcoma of the Spine Mimicking a Psoas Abscess Secondary to Spinal Infection

Abstract: We report a case of Ewing sarcoma that mimicked a psoas abscess secondary to spinal infection. Abnormal magnetic resonance imaging images, as well as a confusing clinical course, made diagnosis difficult. When enlargement of the iliopsoas with a vertebral lesion is detected in a child with low back pain, Ewing sarcoma should be included in the differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 22 publications
0
13
0
5
Order By: Relevance
“…For patients who undergo resection, radiation, and chemotherapy, the 5-year survival rate is 33%. 1,67 The development of effective chemotherapy has been the main factor for overall improvement and disease-free survival among these patients; the 5-year survival rate is 70%. 53 A review of the St. Jude's Children's Research Hospital identified 344 patients with Ewing's sarcoma, of which 33 tumors were primary tumors in the vertebra.…”
Section: Primary Bone Tumors Affecting the Atlantoaxial Skeleton Of Cmentioning
confidence: 99%
“…For patients who undergo resection, radiation, and chemotherapy, the 5-year survival rate is 33%. 1,67 The development of effective chemotherapy has been the main factor for overall improvement and disease-free survival among these patients; the 5-year survival rate is 70%. 53 A review of the St. Jude's Children's Research Hospital identified 344 patients with Ewing's sarcoma, of which 33 tumors were primary tumors in the vertebra.…”
Section: Primary Bone Tumors Affecting the Atlantoaxial Skeleton Of Cmentioning
confidence: 99%
“…This is supported in part by one other case report detailing postoperative extramedullary proliferation after intramedullary nailing of bilateral humeral fractures in a patient with known multiple myeloma. Additionally, as in our patient, a neoplasm can simulate a localized abscess, 12 and a soft-tissue sarcoma can be misdiagnosed as an intramuscular hematoma. In this patient, fluid appearing to be gross purulence at the incision led to an erroneous diagnosis and treatment of an apparent postoperative infection.…”
Section: Discussionmentioning
confidence: 60%
“…Radiographic evidence of calcification is rare with only a few previously described cases of metastases from the long bones or scapula. 5 Once discovered, prompt treatment must be performed to preserve function. Complete surgical removal of primary tumor is the preferred method of local treatment, whenever a marginal or wide resection is possible.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Radiating pain is the most common presenting complaint in patients with spinal tumors. 1,5 Neck pain is a common complaint in the pediatric population. One survey indicates it as the second most common pain in the preadolescent population, and the most persistent pain symptom, recurring in 21% of preadolescents once a month and 6.3% once a week.…”
Section: Introductionmentioning
confidence: 99%